FAKTOR PEMBENTUK VIRALITAS PROMOSI MUSISI INDEPENDEN DI MEDIA SOSIAL - Suciati, Pijar (Jurnal Vokasi Indonesia, 2020)
Successful viral communication depends on the ability of the sender to turn the recipient into an active marketer of the message. Tto be viral, before creating and sending the messages, sender should be considering the receiver's perspective and the content of the message. This study aims to find out how strong the factors forming the viral message that affecting the attitude of the audience towards promotional messages from an indie musician/band (Mocca). The paradigm used in this research is positivist (classic), the methodology is quantitative and explanatory approach. The data collection method is survey with online questionnaire. The analysis model is the Hypothetical Path Diagram. This research find if we want to make our promotional message to be viral, we should pay attention to the elements of the message structure, the contents of the message, and how to deliver the message. In addition we should pay attention to the elements of credibility, attraction, and strength of the message. Specific finding in this study are regarding proximity (proximity) and the psychology of message recipients.